Implementation of the One Day One Ayat Method for Memorizing Short Surahs in Children Aged 5–6 Years: A Case Study at TK IT Mona School - Lailatus Syafa'ati; Rista Sundari (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
This research aims to determine the effectiveness of the One Day One Ayat (ODOA) method in helping children aged 56 years old memorize short letters at TK IT Mona School. This method is applied by memorizing one verse every day accompanied by repeating the previous verse. Research using a descriptive qualitative approach with data collection techniques through observation, interview, and documentation. Research results show that the ODOA method makes children more enthusiastic, consistent, and helps the development of memory and thinking ability. This method also involves the role of teachers and parents in accompanying children. Obstacles such as differences in memorization skills and lack of support from home can be overcome with the right approach from the teacher. The ODOA method is proven to be effective in instilling the habit of memorizing and loving Al-Qur'an from an early age.